Intraductal papilloma of minor salivary gland: a case report and literature review - Yifei Wang; Xiaowei Li; Chunfang Yao; Yi Wu; Hengli Ni (Frontiers in Oral Health)
Intraductal papilloma is a rare benign neoplasm arising from the secretory ducts of the salivary glands. A 79-year-old man with an intraductal papilloma located in the minor salivary gland of sublingual mucosa was reported. The lesion, characterized by extensive internal papillomatous hyperplasia, was confirmed through histopathology and immunohistochemistry. We conducted a literature review to clarify intraductal papilloma and differences between inverted ductal papilloma, highlighting the significance of CK7 and MUC-1 immunohistochemical staining in diagnosing intraductal papilloma.